Submarine landforms reveal varying rates and styles of deglaciation in North-West Greenland fjords - Batchelor, CL; Dowdeswell, JA; Rignot, E (Elsevier, 2018)
An understanding of the former configuration and dynamics of the Greenland Ice Sheet is needed to provide a context for modern observations, to constrain numerical models and to predict the likely future ice-sheet response to climatic change. Whereas previous geophysical investigations of the North-West Greenland margin have focused on the mapping of full-glacial and deglacial landforms on the mid to outer shelf, relatively little is known about more recent ice-sheet dynamics on the inner shelf and in the fjords. We present swath-bathymetric data from the inner shelf and fjords of North-West Greenland. Streamlined subglacial landforms, including ice-sculpted bedrock and mega-scale glacial lineations, reveal the direction of Late Quaternary ice flow through fjords and across the inner shelf. Landforms that are transverse to the former ice-flow direction, including small recessional moraines, major moraine ridges and grounding-zone wedges, show the locations of former still-stands in the grounding zone during regional deglaciation and terminus readvances linked to the Little Ice Age. The distribution of submarine glacial landforms in the inner fjords suggests that the outlet glaciers of North-West Greenland experienced varying rates and styles of ice retreat during the late Holocene, which was probably controlled mainly by fjord water depth.Inner fjords that have contemporary water depths of less than 350 m contain series of small recessional moraines, which indicate the slow retreat of a grounded ice margin. Small recessional moraines are generally absent from inner fjords with water depths of more than 350 m, which are interpreted to have experienced more rapid ice retreat during the late Holocene. During this work, C.L. Batchelor was in receipt of a Junior Research Fellowship at Newnham College, Cambridge. The bathymetric data that was collected during JR175 of the RRS James Clark Ross to West Greenland in 2009 was funded by Natural Environment Research Council (NERC) grant NE/D001951/1 to C. Ó Cofaigh.